Optimalisasi Manajemen Hubungan Pemasok untuk Mendukung Keberlanjutan UMKM Tahu Sutra Kusuka: Optimizing Supplier Relationship Management to Support the Sustainability of Kusuka Silk Tofu MSMEs - Pandya Urdha Sakti; Muhammad Agri Maulana; Rajendra Ataillah Milano; Agus Ristono (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The Kusuka Silken Tofu (Tofu Sutra Kusuka) MSMEs in Sleman, Yogyakarta, face challenges in achieving sustainable production due to dependence on a single soybean supplier and the lack of raw material quality acceptance standards. This condition often results in production delays and decreased product quality. This community service activity aims to optimize supplier relationship management through diversifying raw material sources and implementing simple soybean quality control standards. The methods used include field observations, interviews with MSME owners, participatory discussions, and the development of recommendations to improve supply chain management. The results indicate that implementing supplier diversification and soybean quality acceptance standards reduces supply noise, minimizes the risk of production delays, and maintains consistent silken tofu quality. Thus, this activity helps strengthen the sustainability of soybean-based MSMEs and can serve as a model for developing similar MSMEs in other regions.